Launch of the Climate Security Observatory - Liebig, Theresa Ines (2023)
The CGIAR Research Initiatives on Climate Resilience; Fragility, Conflict, & Migration; and Livestock & Climate, with the CGIAR Focus Climate Security, together with our partners from the UNU Center for Policy Research, Geneva Peacebuilding Platform, and the Geneva Centre for Security Policy, held the launch of the CGIAR Climate Security Observatory at the Geneva Centre for Security Policy on May 23, 2023 in Geneva, Switzerland.